Plasma-surface interaction and mechanisms of dust production in ITER ELM simulation experiments with QSPA Kh-50 - Makhlaj, V.A.; Garkusha, I.E.; Aksenov, N.N.; Byrka, O.V.; Landman, I.; Lebedev, S.I.; Shevchuk, P.B. (Вопросы атомной науки и техники, 2012)
Experimental simulations of ITER transient events with relevant surface heat load parameters (energy density and the pulse duration) were carried out with a quasi-stationary plasma accelerator QSPA Kh-50. The several mechanisms of dust generation from tungsten surfaces were identified. The major cracks development and it bifurcation led to generation dust particles with sizes up to tens μm. Melting of surface and development of fine meshes of cracks along the grain boundaries are accompanied by resolidified bridges formation through the fine cracks. Such bridges produce nm-size dust. Appearance of sub-micron and nanometer-size cellular structures under plasma irradiation can leads to the intensification of the dust formation. Экспериментальное моделирование ИТЭР переходных явлений с соответствующими параметрами тепловых нагрузок на поверхность (плотности энергии и длительности импульса) выполнены в квазистационарном плазменном ускорителе КСПУ Х-50. Были идентифицированы несколько механизмов генерации пыли с поверхности вольфрама. Развитие макротрещин и их бифуркация привели к генерации частиц пыли размером до десятков микрометров. Плавление поверхности и развитие сетки мелких трещин по границам зерен, сопровождаются образованием перезатвердевших мостов через мелкие трещины. Такие мосты создают наноразмерную пыль. Появление субмикронных и наноразмерных ячеистых структур при облучении плазмой может интенсифицировать образование пыли. Експериментальне моделювання ІТЕР перехідних явищ з відповідними параметрами теплових навантажень на поверхню (густини енергії і тривалості імпульсу) виконані в квазістаціонарному плазмовому прискорювачі КСПП Х-50. Були ідентифіковані декілька механізмів генерації пилу з поверхні вольфраму. Розвиток макротріщин і їх біфуркація привели до генерації частинок пилу розміром до десятків мікрометрів. Плавлення поверхні і розвиток сітки дрібних тріщин по границях зерен супроводжуються утворенням перезатверділих мостів через дрібні тріщини. Такі мости створюють нанорозмірний пил. Поява субмікронних і нанорозмірних стільникових структур під час опромінення плазмою може інтенсифікувати утворення пилу.